“Nature and Innovation”: Do appreciation of nature and need for cognition predict intentions to perform sustainable behaviors? - Syurawasti Muhiddin; Yopina Galih Pertiwi (Jurnal Ecopsy, 2022)
Sustainable behavior is a behavior that aims to protect physical as well as human resources. Therefore, it is important to understand the behavior to reduce negative consequences of environmental problems. The study aimed to examine the role of appreciation of nature and the need for cognition on the intention to perform sustainable behavior. This study used a quantitative approach with a survey method. A total of 240 respondents aged 18 – 40 years old completed the online survey. Appreciation of nature scale, need for cognition scale, and intention to act scale were used as data collection instruments. Results showed that appreciation of nature and need for cognition positively predicted the intention to carry out sustainable behavior. Combining the two variables in one model increased predictive power to the intention to perform sustainable behavior. Furthermore, need for cognition had greater predictive power than appreciation of nature. This research showed that affective and cognitive aspects are crucial for the sustainable behavior models. Implications regarding the role of the young generation in supporting sustainable behavior may be further discussed.